Proximal femoral excision with interposition myoplasty for cerebral palsy patients with painful chronic hip dislocation. (August 2015) - Patel, Nirav K.; Sabharwal, Sanjeeve; Gooding, Christopher R.; Hashemi-Nejad, Aresh; Eastwood, Deborah M.
Purpose: Proximal femoral excision is a salvage procedure for painful chronic hip dislocation in cerebral palsy (CP) patients. The primary objective of this article is to describe our experience of an amplified interposition myoplasty, with appropriate peri-operative pain and tone management strategies, in a cohort of non-ambulatory CP patients with painful chronic hip dislocation. Our secondary objective is to present the clinical outcomes of these patients. Methods: We describe our experience in 20 CP patients (25 procedures) at mean 54-month (range 27–169) follow-up with a surgical technique that includes an augmented interposition myoplasty and tone management. The indications for surgery were pain (21 hips), poor sitting tolerance (11) and difficulty with perineal care (8). Results: The mean age was 22 years (range 10–40) with 11 patients Gross Motor Function Classification Scale (GMFCS) IV and 9 patients GMFCS V. Mean length of stay was 13 days (3–35). One procedure required revision at 12 months. Mean pain score improved from 7.8 (5–10) pre-operatively to 2.8 (1–5) post-operatively ( p < 0.001). Sitting tolerance improved in all patients and in 75 % (15) perineal care was easier. Conclusions: Our interposition myoplasty technique with individualised pain/tone management has good outcomes in this cohort of patients with multiple co-morbidities.